2015
DOI: 10.1371/journal.pone.0136935
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Longitudinal Lung Function of Healthy Mexican Children

Abstract: IntroductionOur aim was to estimate the longitudinal effect of Socioeconomic status (SES) on lung function growth of Mexican children and adolescents.Materials and MethodsA cohort of Mexican children in third grade of primary school was followed with spirometry twice a year for 6 years through secondary school. Multilevel mixed-effects lineal models were fitted for the spirometric variables of 2,641 respiratory-healthy Mexican children. Monthly family income (in 2002 U.S. dollars [USD]) and parents’ years comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…The direction of associations between lower maternal education and lung function in our study was unexpected and not consistent with the weight of existing evidence regarding socio‐economic status (SES) and child health . While we do not have a good explanation for these findings, it could be chance findings in the context of multiple comparisons or inaccurate measurement of maternal education.…”
Section: Discussioncontrasting
confidence: 94%
“…The direction of associations between lower maternal education and lung function in our study was unexpected and not consistent with the weight of existing evidence regarding socio‐economic status (SES) and child health . While we do not have a good explanation for these findings, it could be chance findings in the context of multiple comparisons or inaccurate measurement of maternal education.…”
Section: Discussioncontrasting
confidence: 94%
“…From the 33 articles incorporated in this review, 27 used education as the socioeconomic indicator, or as part of an index of socioeconomic circumstances; reporting mainly both parents’ education29 31 32 35–39 44 47–51 or the mothers’ education 9 37 40–42 46 52–54. Occupation and income were reported in 12 studies, mainly as both parents’ occupation30 35 36 38 44 46 47 53 and family or household income 6 31 35 36 39 41 42 44 50 51…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies reported estimates for FEV 1 , either as mean values of volume,6 9 10 30 35 36 46 48–50 52 54 mean difference,34 44 46 percentages,29 39 percentage of predicted,31 37 38 40–43 45 46 51 53 55 percentage of change,7 32 33 56 z-scores,8 45 and/or the relation between FEV 1 and FVC 29 30 33 35 37 47 50…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is the lack of socioeconomic data, in particular, on parental level of education and income, as well as on environmental factors, because these unquestionably influence lung development and may explain, in part, the differences observed in lung function among the white, black, and brown children in our sample. 21 , 22 It is also noteworthy that we employed conventional multiple linear regression, in which it is assumed that the variance is homogeneously distributed over the height and age range. This problem was mitigated by the log transformation of the data and because a narrow age range was assessed.…”
Section: Discussionmentioning
confidence: 99%